PENGARUH PENGGUNAAN BAHAN AJAR BERBASIS MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA KELAS IV DI SDN RANDEGAN DAWARBLANDONG - GIGIH KUSBAHTIAR, MOHAMMAD (Jurnal Penelitian Pendidikan Guru Sekolah Dasar, 2019)
Pendidikan merupakan suatu usaha sadar dan terencana untuk mewujudkan suasana belajar dan proses pembelajaran agar peserta didik secara aktif mengembangkan potensi dirinya. Berdasarkan hasil observasi melalui pengamatan langsung proses pembelajaran di kelas empat SDN Randegan Dawarblandong, guru belum mengembangkan pembelajaran secara optimal selaa proses pembelajaran. Salah satu alternative cara yang dapat digunakan oleh guru adalah bahan ajar berbasis model pembelajaran inkuiri. Tujuan yang ingin dicapai dari penelitian ini adalah untuk mengetahui bagaimana pengaruh bahan ajar berbasis model pembelajaran inkuiri terhadap hasil belajar IPA kelas materi ?Bagian dan Fungsi Tubuh Tumbuhan?. Penelitian ini merupakan penelitian eksperimen dengan jenis quasy eksperimen. Desain penelitian yang digunakan dalam penelitian ini adalah non-equivalent control design. Pelaksanaan penelitian ini melalui tiga tahapan yakni pretest, treatment dan posttest. Lokasi penelitian bertempat di SDN Randegan Dawarblandong. Populasi pada penelitian ini ialah seluruh siswa kelas empat. Penelitian dilaksanakan bulan Juli 2019. Berdasarkan perhitungan uji t-test indendent diatas, diperoleh nilai thitung sebesar -2,269. Jika nilai thitung dibandingkan dengan nilai ttabel, maka hasil yang diperoleh yaitu thitung (-2,269) < ttabel (-2,00). Terdapat pengaruh yang signifikan dalam penggunaan bahan ajar berbasis model pembelajaran inkuiri. Nilai gain ternormalisasi pada kelas ekperimen diperoleh skor sebesar 0,634 termasuk dalam kategori sedang dan terdapat pengaruh signifian dalam penggunaan bahan ajar berbasis model pembelajaran inkuiri terhadap hasil belajar IPA kelas empat di SDN Randgan Dawarblandong. Kata Kunci: pengaruh, bahan ajar, inkuiri, hasil belajar.Education is a conscious and deliberate effort to create a learning atmosphere and learning processes. So that, the learnersare actively developing their potential. Based on the observation through direct observation of the learning process in the fourth grade at SDN Randegan Dawarblandong, teachers didn?t use learning materials effectively while the studying activity was on going in the class. This case affected student?s understanding on the materials and it impacted on an achieved the student?s learning outcomes. Based on the description above. It?s necessary to use interesting learning materials in order to increase student?s motivation in paying attention to the materials which was being taught. An alternative which can be use is learning materials. The purpose of this study was to describe how the effect of using learning materials based on inquiry learning model towards learning outcomes of fourth grader?s science subject especially ?The Part and Function of Plant?. This study was an experimental study with quasy experiment-type. The design of study that use in this study are non-equivalent control design. Implementation of this study through three stages namely pretest, treatment and posttest. The location of this study is located at SDN Randegan Dawarblandong. Population of this study was all the students of fourth grade. Study conducted on July, 2019. Data collecting techniques which applied was instrument trial and data processing. Instrument trial was applied, meanwhile the processing data using normality test, homogeneity test, and t-test. Based on the calculation indendent, the result of t-count is -2,269. If t-count compared with the result of t-table, then the result of obtained were t-count (-2,269) < t-table (-2,00). There was a significant effect of using learning materials based on inquiry learning model so it performed normalization gain test to determine the amount of student?s learning outcomes improvement before and after learning process existed both on control class and experiment class. Normalized gain score on experiment class that obtain 0,634. Gain score interpretation belong to middle category, since score which obtain between 0,3 and 0,7. It showed that there was a significant effect of using learning materials based on inquiry leraning model towards learning outcomes of fourth grade?s science subject at SDN Randegan Dawarblandong.. Keywords: effet, learning materials, inquiry, leaning outcomes